The Influence of Listening an Islamic Religious Dialogue Programme at RRI towards Religious Practice in Muara Dua Lhokseumawe (Pengaruh Mendengar Acara Dialog Agama Islam di RRI Terhadap Pengamalan Agama Masyarakat di Muara Dua Lhokseumawe - fauzi abubakar (Jurnal Pekommas, 2016)
Radio has a big influence in the broadcasting Islam because it can affect the community to practice religion in his life. Islamic religious dialogue is one form of religious broadcasts on RRI Lhokseumawe that many get a response from the listener. The problem in this study is whether there is influence hear the dialogue of Islam against the practice of religion communities in Muara Dua Lhokseumawe. Indicators of variable hear the dialogue of Islam (X) is a broadcasting frequency, duration, time broadcasting, speakers, and broadcast material. While indicators of public religious practice (Y), that is prayer, fasting, zakat and donations. The research uses descriptive quantitative research methods. The research data were taken using a questionnaire, then the data is processed and analyzed descriptively and statistically. Used theoretical basis is communication theory used as framework in this research is the theory of stimulus organism response (SOR), of Hovland, Janis and Kelley who explained that the process of change of attitude is similar to the learning process. The results showed that 4.1% of society are affected by religious practice to hear the dialogue of Islam in RRI and the rest influenced by other factors.Radio mempunyai andil yang cukup besar dalam penyiaran agama Islam karena dapat mempengaruhi masyarakat dalam mengamalkan ajaran agama dalam kehidupannya. Acara dialog agama Islam merupakan salah satu siaran agama di RRI Lhokseumawe yang banyak mendapat respon pendengar. Permasalahan penelitian ini adalah apakah ada pengaruh mendengar acara dialog agama Islam terhadap pengamalan agama masyarakat di Muara Dua Lhokseumawe? Indikator dari variabel mendengar acara dialog agama Islam (X) yaitu frekuensi penyiaran, durasi, waktu siar, narasumber, dan materi siaran. Sementara indikator pengamalan agama masyarakat (Y), yaitu shalat, puasa, zakat dan infak. Penelitian menggunakan metode penelitian kuantitatif deskriptif. Data penelitian diambil dengan menggunakan angket, kemudian data diolah dan dianalisis secara deskriptif dan statistik. Landasan teori yang digunakan adalah Teori komunikasi yang digunakan sebagai kerangka pikir dalam penelitian ini yaitu teori stimulus organisme response (SOR), dari Hovland, Janis dan Kelley yang menjelaskan bahwa proses perubahan sikap adalah serupa dengan proses belajar. Hasil penelitian menunjukkan bahwa 4,1% pengamalan agama masyarakat dipengaruhi oleh mendengar acara dialog agama Islam di RRI dan sisanya dipengaruhi oleh faktor-faktor lain.